Human-induced Alterations of the Mycobiota in an Alpine Show Cave (Italy, SW-Alps) - Mammola, Stefano; Di Piazza, Simone; Ziotti, Mirca; Badino, Giovanni; Marco, Isaia (Acta Carsologica, 2017)
Anthropogenic alterations in show caves are well documented in scientific literature. One of the main sources of perturbation derives from visitors, acting as carriers of propagules and organic matter in the cave ecosystems. Such perturbation generally results in a significant alteration of the natural subterranean microbiota. In this study, we characterize the mycobiota of the superficial alluvial sediment (0–5 cm) of the Bossea show cave (NW-Italy) over two sampling seasons, aiming to investigate whether anthropogenic rather than natural factors contribute to the colonization and proliferation of alien mycobiota in the cave environment. We placed eighteen sampling plots at different distances from the touristic pathway that crosses the cave. The distance from the touristic pathway was used as proxy to sort the sampling plots in three groups according the degree of anthropogenic disturbance (high: 0–2 m; intermediate 2–40 m; low: >100 m). Moreover, in order to elucidate the potential effect of other factors, we introduced in our analysis the distance from the subterranean river and the distance from the cave entrance. In each plot, we collected two samples of alluvial sediment, in winter and summer. Fungi were isolated from each sample and identified by means of an integrated morphological approach. We observed a rich and diversified fungal community – 63 taxa of Zygomycota and Ascomycota plus several unidentified yeasts – consisting of both native and alien species. Regression analysis points out a decrease of the abundance and the diversity of viable propagules at increasing distances from the touristic pathway rather than the cave entrance or the subterranean river. Accordingly, the exogenous organic materials passively conveyed by tourists, possibly explains the higher proliferation of alien species in the proximity of the touristic pathway. There was also a seasonal variation in the diversity and abundance of propagules, which we interpreted in light of the peculiar microclimate of the cave. In a second step, we used Indicator Species Analysis to identify the most representative species of the different levels of anthropogenic disturbance. In particular, Aspergillus spelunceus was found to be indicator of low disturbance, whereas Mucor corticola and A. asperescens were found to be indicators of intermediate and high disturbance, respectively. Key words: anthropic disturbance, alluvial sediment, alien species, airborne fungi, environmental impact.